Heme induces intestinal epithelial cell ferroptosis via mitochondrial dysfunction in transfusion‐associated necrotizing enterocolitis. Issue 12 (16th November 2022) - Dang, Dan; Meng, Zhaoli; Zhang, Chuan; Li, Zhenyu; Wei, Jiaqi; Wu, Hui
Abstract: Transfusion‐associated necrotising enterocolitis (TANEC) is a life‐threatening disease with a poor prognosis in preterm infants. This study explored whether and how heme induces ferroptosis in TANEC gut injury. A TANEC mouse model and a cell culture system for heme and Caco‐2 cells were established. Ferroptosis was assessed by measuring iron and malondialdehyde (MDA) levels and mitochondrial morphology in intestinal tissues and Caco‐2 cells. Mitochondrial dysfunction was evaluated by measuring mitochondrial reactive oxygen species (ROS) production and membrane potential using JC‐1. The intestinal injury grade was higher in the anemia‐transfusion group than in the control group ( p  < .0001). Higher intestinal iron concentration ( p  < .0001), elevated levels of lipid peroxidation MDA ( p  = .0021), and ferroptotic mitochondrial morphological changes were found in mice of the anemia‐transfusion group; specific ferroptosis inhibitor could alleviate anemia‐transfusion gut injury, suggesting that ferroptosis play a role in the TANEC gut injury. Next, we explored whether heme released by hemolysis of erythrocytes induces ferroptosis in intestinal epithelial cells in vitro. The viability of Caco‐2 cells significantly decreased after heme treatment ( p  < .0001). Iron accumulation, MDA elevated levels, and mitochondrial dysfunction also existed in the co‐culture system, which ferroptosis inhibitors could reduce. In summary, ferroptosis was discovered in TANEC, and heme could induce ferroptosis in intestinal epithelial cells via mitochondrial dysfunction. Heme‐inducing ferroptosis may be a possible mechanism and therapeutic target for TANEC. Abstract : Heme induces intestinal epithelial cell ferroptosis in transfusion‐associated necrotizing enterocolitis.